From The Magic Tree: The Miracle of Oud Oil (Essential Oils for Healing Part 1) - Puteri Fadzline, Muhamad Tamyez; Fazeeda, Mohamad; Cheng, Jack Kie (2017)
YOU MIGHT HAVE HEARD OF THIS WORD: OUD or Oudh or Agarwood or Gaharu (as it is known in Malaysia) or chénxiāng/ Cham Heong as it is known in Chinese. But more than its proper name, you might have heard it described by a myriad of divine metaphors like: “Scent from Heaven”, “Wood of God”, “Sacred Aroma”, “Scent of Nirvana” or “Ambrosial Fragrance”. Whatever its moniker – from Oud comes “The Smell of Musky Luxury” as headlined in an article of the same name in Fortune Magazine. Indeed, it is the bouquet of royalty, eminence, prestige and station in life. Not all can afford to wear a whiff of it. For Oud is, after all, the most expensive essential oil in the world.